Побудова креативних зразків у галузі моди за допомогою GAN мереж - Титечко, П. В. (ХНУРЕ, 2023)
This thesis outlines the usage of GAN networks as a tool to generate creative fashion samples that can be used in a variety of applications, such as designing new fabric patterns or materials. By training a GAN on a dataset of existing fabric patterns, the generator can learn how to generate patterns that look similar to the ones in the training dataset, yet with some variations that make these new patterns unique. Besides uniqueness we are looking for possibility to generate creative content, the one which is aesthetically appealing and narrow infinite possibilities in the creative space. Suggested approach is based on experiments with loss function and noise vector generation.
Keywords: GAN мережі; машинне навчання; генерація зображень